2017
DOI: 10.5472/marumj.370642
|View full text |Cite
|
Sign up to set email alerts
|

The morphological and biochemical investigation of prenatal electromagnetic wave effects on urinary bladder in rats

Abstract: The morphological and biochemical investigation of electromagnetic wave effects on urinary bladder in prenatal ratsPrenatal sıçan mesanesi üzerine elektromanyetik dalganın etkilerinin morfolojik ve biyokimyasal olarak incelenmesi ÖZ Amaçlar: Bu çalışmanın amacı, dijital mobil telefonlarından gelen ve en yüksek spesifik absorbsiyon oranı (Specific Absorbtion Rate-SAR) değeri 1,79W/kg olan dijital selüler sistem (DSS) 1800-MHz radyasyonunun erkek sıçan mesanesi üzerine etkilerini araştırmaktır.Gereç ve Yöntem: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In another prenatal study, electromagnetic waves emitted from cell phones were shown to damage the blood-testis barrier and cause a decrease in the amount of ZO-1 protein distribution, loss of germ cells, an increase in apoptotic cells, a decrease in serum testosterone level, and an increase in oxidative stress in the testes [19,20]. In addition, electromagnetic waves emitted by mobile phones have been shown to cause tight junction degeneration starting from intrauterine life, with a decrease in ZO-1 intensity in the urothelium, an increase in degranulated mast cells, and an increase in oxidative stress in the urinary bladder [21] and neuronal injury with oxidative stress increase in the brain [22]. It is impossible to avoid mobile phone technology, especially with the current COVID-19 pandemic where children, adults, and even pregnant women are using them for many purposes such as communication, education, etc.…”
Section: Alteration Of Blood-testis Barrier In Various Testicular Inj...mentioning
confidence: 99%
“…In another prenatal study, electromagnetic waves emitted from cell phones were shown to damage the blood-testis barrier and cause a decrease in the amount of ZO-1 protein distribution, loss of germ cells, an increase in apoptotic cells, a decrease in serum testosterone level, and an increase in oxidative stress in the testes [19,20]. In addition, electromagnetic waves emitted by mobile phones have been shown to cause tight junction degeneration starting from intrauterine life, with a decrease in ZO-1 intensity in the urothelium, an increase in degranulated mast cells, and an increase in oxidative stress in the urinary bladder [21] and neuronal injury with oxidative stress increase in the brain [22]. It is impossible to avoid mobile phone technology, especially with the current COVID-19 pandemic where children, adults, and even pregnant women are using them for many purposes such as communication, education, etc.…”
Section: Alteration Of Blood-testis Barrier In Various Testicular Inj...mentioning
confidence: 99%